PENGARUH FINANCIAL DEVELOPMENT, INVESTASI ASING LANGSUNG DAN URBANISASI TERHADAP KETIMPANGAN PENDAPATAN DI INDONESIA - Restulillah, Fajar Hendito; Ariusni, Ariusni (Universitas Negeri Padang, 2020)
Abstract : This study aims to determine the effect of financial development on incomeinequality in Indonesia. The influence between foreign direct investment and incomeinequality in Indonesia. The influence between urbanization and income inequality inIndonesia. The data in this study uses secondary data from 1981 to 2018 obtained fromthe BPS and World Bank websites. This study uses multiple linear regression models. Aswell as data analysis used, namely descriptive analysis and inductive, in inductiveanalysis there are several tests in it including: (1) Ordinary Least Squares (OLS) test, (2)Classical Assumption Test (3) Error Correction Model (ECM)(4) Final results of longtermequations, (5) Hypothesis Test. The results of this study found that in the long termfinancial development has a significant positive effect, foreign direct investment has asignificant negative effect and urbanization has a positive and significant effect onincome inequality in Indonesia. Meanwhile, in the short term financial development has apositive and insignificant effect, foreign direct investment has no significant positiveeffect and urbanization has a negative and insignificant effect on income inequality inIndonesia.Keyword : Financial Development, Foreign Direct Investment, Urbanization and IncomeInequality